Ananda - Chandra, L. (Искусство Евразии, 2021)
This article is about the meanings and iconography of the deity Ananda. Famous images from Japanese, Chinese and Indian treatises and other sources are given. The translation of Lokesh Chandra's article from the Dictionary of Buddhist Iconography was made by S.М. Belokurova.